2015
DOI: 10.4194/1303-2712-v15_2_08
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Reproductive biology of Mediterranean cuttlefish Sepia elegans has been studied in the Aegean Sea from total of 924 animals (432 males, 492 females) caught during monthly trawl surveys from May 2008 to April 2009. Cuttlefishes were measured, weighed, maturity assessed, and reproductive systems were removed and investigated in the lab. The size at maturity (ML 50 ) were 42 mm (males) ML and 41mm ML (females) respectively. Seasonal changes in a gonadosomatic index suggest extended reproductive period of the popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…These two species have been markedly less studied in recent years than S. officinalis. Of three studies on S. elegans published during 2013-2019, a large-scale study of its reproductive biology in the East Mediterranean revealed a number of differences from the West Mediterranean and Atlantic Ocean (Salman, 2015a). Dance et al (2014) confirmed differences in the spawning and nursery ground locations of the three Mediterranean cuttlefish species (S. officinalis, S. elegans and S. orbignyana) based on stable isotope analysis of cuttlebone.…”
Section: Sepia Elegans and S Orbignyanamentioning
confidence: 75%
“…These two species have been markedly less studied in recent years than S. officinalis. Of three studies on S. elegans published during 2013-2019, a large-scale study of its reproductive biology in the East Mediterranean revealed a number of differences from the West Mediterranean and Atlantic Ocean (Salman, 2015a). Dance et al (2014) confirmed differences in the spawning and nursery ground locations of the three Mediterranean cuttlefish species (S. officinalis, S. elegans and S. orbignyana) based on stable isotope analysis of cuttlebone.…”
Section: Sepia Elegans and S Orbignyanamentioning
confidence: 75%
“…The oogenesis of S. esculenta was previously, and incorrectly, described as asynchronous [29]. The ovulation pattern of some other Sepiida species has also often been described as asynchronous [13,16,28]; however, observations of the oocyte phase distribution have shown the predominance of small yolkless oocytes in many Sepia spp., such as S. officinalis [28], S. opipara (Iredale, 1926 [61]), S. rozella (Iredale, 1926 [61]), S. plangon (Gray, 1849 [62]) [27], S. elegans (Blainville, 1827 [63]) [16], and S. orbignyana (Ferussac [in d 'Orbigny], 1826 [64]) [13]. This indicated that the ovulation patterns of the following species could also be described as group-synchronous.…”
Section: Female Reproductive Systemmentioning
confidence: 99%
“…Despite the wide distribution of cuttlefish and their high commercial value, data on their reproductive biology are scarce. Most studies connected to the reproductive biology of cuttlefish have been focused on the following: the determination of the sex ratio; spawning seasons; their size at first maturity and sizes at different maturity stages; the monthly distribution of maturity stages; the calculation of certain reproductive indices; and the development of maturity scales for individual species [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Female reproductive biology has been studied in more detail than that of males.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphometrically S. prabahari closely resembles the juveniles of Sepia pharaonis; with the exception of the arm length, tentacular club, sucker ring size and pattern, dorsal mantle pattern and cuttlebone. Reproductive aspects of commercially important cephalopods in general (see reviews by Pierce et al, 2010;Jereb et al, 2015;Lishchenko et al, 2021) and Sepia in particular (Dursun et al, 2013;Salman, 2015;Gras et al, 2016;Sifner et al, 2018;Lin et al, 2019) have been studied in recent years. There is no detailed description on the biology of S. prabahari and the only report is on their population characteristics (Singh, 2005).…”
Section: Introductionmentioning
confidence: 99%